Pengaruh Iklim Komunikasi Organisasi Terhadap Kohesivitas Kelompok Karang Taruna Tunas Jaya: (Studi Deskriptif Kuantitatif di Desa Mekar Jaya, Ciawi Gebang Kuningan) - Rizki Budhi Suhara; Yusuf Supari (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2021)
The presence of youth organizations in the community of Mekar Jaya Ciawi Gebang Village has shown its positive role, but it is not yet maximized. The core management of the youth organization has made improvements and changes to the structure to maximize the roles and functions of members to be more active and show good communication so that they can foster a sense of togetherness and cohesion among other members. This study has the following objectives: 1) to find out how the influence of organizational communication climate on Karang Taruna Tunas Jaya, 2) to find out how the influence of group cohesiveness on Karang Taruna Tunas Jaya, 3) to find out how much influence organizational communication climate has on group cohesiveness Karang Taruna Tunas Jaya. The research methodology used is descriptive quantitative with survey method. The population of this study amounted to 60 people using census sampling technique. The research data processing technique uses descriptive inferential statistics, namely the average score value to calculate the value of the frequency distribution, while to calculate the correlation using Spearman rank correlation statistics, one-way hypothesis testing with t-test and determinant coefficients. The results of this study are: 1) the influence of organizational communication climate on Karang Taruna Tunas Jaya is classified as good, the results show an average value of 47.3 where the value after entering the range of 40.8 - 50.4 so that it is declared good, 2) the effect of cohesiveness group at Karang Taruna Tunas Jaya is good where the results of the study show an average value of 63.51. This value is included in the interval table in the range of 54.4 - 67.2 so that it can be declared good, 3) the value of the influence of the organizational communication climate on group cohesiveness is 0.376 or 14.1% while the remaining 85.9% is influenced by other factors that are not discussed in this study.